Spectatorship : shifting theories of gender, sexuality, and media - Samer, Rox, 1986-; Whittington, William (William Brian) (University of Texas Press, 2017)
"Designed for classroom use, this anthology of influential articles from Spectator, the highly regarded film studies journal published by USC's School of Cinematic Arts, offers historical perspectives on the intersections of gender, sexuality, and media spectatorship"--Publisher's website.